Import dependence of the Irish economy during decade of '60s - Farley, Noel J.J. (Economic & Social Studies, 1978)
Was there a movement to growing import dependence in the Irish economy during the 1960s? Why? These are the central questions for which answers will be sought in this paper. Various measures of import dependence will be introduced, efforts will be made to sort out the roles of changing demand patterns and input coefficients in determining the direction of movement in Irish imports and some suggestions as to the causes of these observed movements will be provided. We will explore the ramifications of the findings for policy formulation and the future of the Irish economy.
Keywords: Irish economy - 1960s; Import dependence - Ireland